THE EFFECT OF PROFITABILITY, SIZE AND LIQUIDITY, TO THE VALUE OF THE COMPANY WITH THE CAPITAL STRUCTURE AS INTERVENING VARIABLES - Adam, Mohamad; Taufik, Taufik; Hamarzonnanda, Hamarzonnanda (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study examined the influence of profitability, size, and liquidity on firm's value with Fund structure as the intervening variable of empirical study on infrastructure, utility, and transportation sector stocks in Indonesia. The aim of this study is to know: The effects of profitability (ROA), size (in Aktiva), and liquidity (CR) to firm's value (PBV). The effects of profitability (ROA), size (in Aktiva), and liquidity (CR) to Fund structure (DER). The effects of profitability (ROA), size (in Aktiva), and liquidity (CR) to firm's value (PBV) with Fund structure (DER) as the intervening variable. Samples in this study were 41 Indonesian companies in infrastructure, utility, and transportation sectors in 2012-2016. Samples were chosen by using purposive sampling method. Data were analyzed by using path analysis with the help of AMOS 22. From the analysis it can be seen that : ROA has negative and significant effects on DER. SIZE has positive and significant effects on DER. CR has negative and significant effects on DER. DER and ROA have positive and significant effects on PBV. CR and SIZE have no effects on PBV. DER is able to mediate the effects of SIZE and CR on firm’s value. DER is unable to mediate the effects of ROA on firm’s value. As the implication, the company has to pay more attention to ROA, size, CR, and DER because they have very important role on the rise or fall of company's performance. The company's performance is important to invite investors to invest their funding in infrastructure, utility, and transportation sectors in Indonesia.